Optimization Of Web Based Academic Information System Design To Increase Efficiency In Junior High Schools - Prasetyo Eka Putra, Fauzan; Moh Riski; Riyan; Yayu Rahma Febriani; Muhammad Umar Mansyur (Jurnal Informasi dan Teknologi, 2024)
School is a system consisting of components that are interrelated and influence each other to achieve one goal. In an effort to achieve school goals, a lot of data processing is carried out. However, middle school academic data processing, especially around me, is still done manually and is still less effective and efficient. Manual processes are error-prone, time-consuming, and often lead to data inconsistencies. By designing this web-based academic information system, it is hoped that it can increase efficiency and effectiveness in processing data and accessing data quickly. The design of this system is expected to be able to manage student data, teacher data, class data, schedule data and student grade data efficiently. Web-based solutions provide the flexibility to access the system from anywhere, which is especially useful for teachers, students and administrative staff. This accessibility will facilitate better communication and collaboration between all stakeholders in the school environment. Additionally, features such as automatic report generation, attendance tracking, and real-time updates will significantly reduce the administrative workload and allow teachers to focus more on educational activities. By implementing this web-based academic information system, the school environment is expected to experience positive impacts, including increased data accuracy, better resource allocation, and increased decision-making abilities. Ultimately, the system aims to support the school's mission of providing quality education and fostering an environment where students can thrive academically. The successful implementation of this system will become a model for other schools that want to modernize their academic data management processes